Investigations into traditionally managed Djallonke-sheep production in the humid and subhumid zones of Asante, Ghana. III. Relationship between birth weight, preweaning growth, and postweaning growth of Lambs - London, J.C.; Weniger, J.H. (Wiley, 1995)
Birth weight, which is subject to difference to prenatal nutrition, increased with parities to the fifth among the subhumid zone (SH = 1.89 kg) dams and to the sixth among the humid zone (H = 1.71 kg) dams. Seasonal influence did not significantly affect birth weights in either zone. Litter type had the greatest influence on birth weight, growth rate, and viability at 60 days of age, among lambs in both zones. The dual advantage of higher birth weights of lambs and higher postpartum weight of their dams, with the benefit of the maternal effect that supported optimal postnatal development lambs, resulted in higher body-weight gain at 60 days of age at sixth parity (H = 6.17 kg; SH = 6.99 kg). In both zones, viability was optimum at the fifth parity (H = 95.0%; SH = 95.6%). For all the weight traits, single lambs (H = 7.73 kg; SH = 8.48 kg) were significantly (p